2000
DOI: 10.1159/000015583
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase RAC3 gene is located within chromosome band 17q25.3 outside and telomeric of a region commonly deleted in breast and ovarian tumours

Abstract: The closely related small GTP-binding proteins Rac1, Rac2, and Rac3 are part of a larger Rho subfamily of Ras proteins. Because disruption of Ras signaling pathways is relevant to the pathogenesis of a wide variety of cancers, it is important to clearly define the structural and functional characteristics of the participating proteins and their encoding genes. Rho subfamily members are involved in a range of signal transduction pathways relevant to cell growth, differentiation, motility, and stress, and Rac pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…It is localized to the membrane to a higher degree than is Rac1 (Mira et al, 2000). Furthermore, it is hyperactive in breast cancers (Mira et al, 2000) and the Rac3 gene is close to a region of chromosome 17 that is often deleted in breast cancers (Morris et al, 2000), which might deregulate its expression.…”
Section: Rhoa ---Mkqepvkpeegrdmanrigafgymecsaktkdg-vrevfematraalq----mentioning
confidence: 99%
“…It is localized to the membrane to a higher degree than is Rac1 (Mira et al, 2000). Furthermore, it is hyperactive in breast cancers (Mira et al, 2000) and the Rac3 gene is close to a region of chromosome 17 that is often deleted in breast cancers (Morris et al, 2000), which might deregulate its expression.…”
Section: Rhoa ---Mkqepvkpeegrdmanrigafgymecsaktkdg-vrevfematraalq----mentioning
confidence: 99%
“…Rac2 is hematopoietic-cell-specific, whereas Rac1 is widely expressed. Rac3 is present in neurons as well as malignant tissue (Haataja et al, 1997;Morris et al, 2000). As osteoclasts express Rac1 and Rac2, we investigated whether these GTPases regulate the bone resorbing capacity of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of Rac3, closely related to Rac1, has also been detected in breast cancer (Mira, Benard et al 2000). Rac3 maps to chromosome band 17q25.3, a region known to contain candidate tumor suppressor genes both in breast and ovarian cancers (Morris, Haataja et al 2000). Highly proliferative breast cancer cells, T47D and MCF-7, but not normal breast cell lines, contain constitutively active Rac3 in a Ras-independent manner (Morris, Haataja et al 2000).…”
Section: Rac Gtpases In Breast Tumorsmentioning
confidence: 99%
“…Rac3 maps to chromosome band 17q25.3, a region known to contain candidate tumor suppressor genes both in breast and ovarian cancers (Morris, Haataja et al 2000). Highly proliferative breast cancer cells, T47D and MCF-7, but not normal breast cell lines, contain constitutively active Rac3 in a Ras-independent manner (Morris, Haataja et al 2000). It has also been shown that expression of a dominant negative mutant Rac3 (N17) leads to inhibition of S-phase entry and cellular proliferation in breast tumor cells, which indicate that Rac3 may promote cell growth (Leung, Nagy et al 2003).…”
Section: Rac Gtpases In Breast Tumorsmentioning
confidence: 99%